2021
DOI: 10.1116/6.0001198
|View full text |Cite
|
Sign up to set email alerts
|

Impact of trimethylaluminum exposure time on the mechanical properties of single-cycle atomic layer deposition modified cellulosic nanopaper

Abstract: Cellulosic nanomaterials can improve the performance of various products and can be renewably sourced. In this study, nanocellulosic paper (nanopapers) is chemically and physically altered with simple gas-phase processing to achieve enhanced mechanical performance. Cellulosic nanofibril paper is exposed to single cycles of trimethylaluminum (TMA) and water to modify the surface and subsurface chemistry with small quantities of aluminum oxide. Precursor exposure times are found to significantly influence the am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…They reported that longer trimethylaluminum exposure durations considerably increased the nanopaper's tensile strength. They also showed that the NC paper became more hydrophobic after being treated with 1cy-ALD (Li and Losego 2021). It should be noted that the WVTR results obtained were not consistent with one another and that the fragile and degradation characteristics of Al2O3 films influenced the barrier properties' stability.…”
Section: Excess Second Precursor and By-products Are Purgedmentioning
confidence: 95%
See 1 more Smart Citation
“…They reported that longer trimethylaluminum exposure durations considerably increased the nanopaper's tensile strength. They also showed that the NC paper became more hydrophobic after being treated with 1cy-ALD (Li and Losego 2021). It should be noted that the WVTR results obtained were not consistent with one another and that the fragile and degradation characteristics of Al2O3 films influenced the barrier properties' stability.…”
Section: Excess Second Precursor and By-products Are Purgedmentioning
confidence: 95%
“…They state that a thin Al2O3 barrier coating on the surface of fibrous cellulose material effectively inhibits oxygen transport and spontaneous combustion of cellulose, but they made no mention of a water vapor barrier (Omerzu et al 2018). Li and Losego (2021) modified NC paper (nanopapers) chemically and physically with simple gas-phase processing. They reported that longer trimethylaluminum exposure durations considerably increased the nanopaper's tensile strength.…”
Section: Excess Second Precursor and By-products Are Purgedmentioning
confidence: 99%